Choices in Quantifying Carbon for Jurisdictional REDD+ : Overview from the Forest Carbon Partnership Facility - Neeff, Till; van der Linden, Marco; Herrick, Moon (World Bank, Washington, DC, 2021)
The Carbon Fund of the Forest Carbon Partnership Facility (FCPF) is set up to pilot performance-based payment systems for emission reductions generated from REDD+ efforts in developing countries.. The piloting efforts include setting a good practice benchmark for robust carbon quantification that is fit for the purpose of attracting performance-based payment. An analysis of the choices that the country programs in the Carbon Fund make in quantifying carbon shows an emerging picture of what is currently feasible in terms of quantifying emissions and removals for REDD+. The impact of the Carbon Fund on the larger REDD+ process is only just beginning to be visible. The good practice benchmark set by the Carbon Fund can also inform the carbon quantification choices of countries that do not participate in the Carbon Fund. The data sets and approaches described in this paper represent what countries had been able to achieve by early 2020 with ample access to technical support, strong motivation from the prospect of results-based payments, and when working at the scale of subnational jurisdictions. The lessons learned from the Carbon Fund’s work in this area can help raise the standard for all countries in their efforts to attract results-based payments for REDD.